Biogas from abattoirs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Transpaille, a plant set up in the abattoirs of Thies in Senegal, is transforming waste products into gas and compost. More than a tonne of animal intestine and gut is fermented daily in a 'digester' vat of 40m3. The decomposed waste makes fine...